High nonlinear coefficient SnO2 varistors tailored by Mn2O3 doping. (October 2020) - Liu, Dongji; Wang, Weiqing; Wang, Feng; Cheng, Kuan; Xie, Qingyun; Zhou, Yuanxiang; Zhao, Hongfeng
Abstract: The SnO2 varistor ceramic with good electrical performance was accomplished. The electrical properties of SnO2 varistor ceramics were systematically studied as a function of Mn2 O3 doping between a loading range of 0.00 and 0.06 mol%. At a dopant of 0.04 mol%, a maximum nonlinear coefficient of 51 is obtained at a sintering temperature of 1400 °C, with the voltage gradient of 453 V/mm and leakage current of 4.2 μA/cm 2 . Highlights: SnO2 varistor ceramic with high nonlinear was obtained by doping Mn2 O3 . Mn-doping increases the potential barrier and further enhances the nonlinear coefficient. α, J L, and E 1mA of SnO2 varistor samples sintered were 51, 4.2 μA/cm 2, and 453 V/mm, respectively. Optimal Mn additive amount suggested as 0.04 mol%.